2005
DOI: 10.1186/1860-5397-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,6-trans-disubstituted 5,6-dihydropyrans from (Z)-1,5-syn-endiols

Abstract: Certain (Z)-1,5-syn-diols 2 may be converted into 2,6-trans-5,6-dihydropyrans by using phosphonium salt 4 or phosphorane 5 as dehydrating agents. A more general four step procedure converts the (Z)-1,5-syn-endiols into enantiomeric dihydropyrans ent-3 via regioselective silylation of the allylic alcohol unit followed by mesylate formation and base-promoted nucleophilic displacement.Page 1 of (page number not for citation purposes) 6 FindingsWe recently reported a one-pot double allylboration reaction sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In our case we were not able to remove stoichiometric amounts of OP(OEt) 3 (which is more hydrophilic than OP(OiPr) 3 ) through an aqueous work up (without saponification). Moreover, pentavalent P(OEt) 5 prepared from P(OEt) 3 with diethylperoxide and ethylbenzenesulfonate, respectively, in an additional step, was reported to effect cyclodehydration of diols to furans and pyrans [4748] (for recent examples for cyclodehydration protocols see [4950]). Thereby, the volatile products were separated from O=P(OEt) 3 through distillation.…”
Section: Introductionmentioning
confidence: 99%
“…In our case we were not able to remove stoichiometric amounts of OP(OEt) 3 (which is more hydrophilic than OP(OiPr) 3 ) through an aqueous work up (without saponification). Moreover, pentavalent P(OEt) 5 prepared from P(OEt) 3 with diethylperoxide and ethylbenzenesulfonate, respectively, in an additional step, was reported to effect cyclodehydration of diols to furans and pyrans [4748] (for recent examples for cyclodehydration protocols see [4950]). Thereby, the volatile products were separated from O=P(OEt) 3 through distillation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to apply this method to the synthesis of structurally complex targets, including natural products, it is sometimes necessary to differentiate the two alcohols that result from the one-pot double allylboration reaction . We have previously reported that the allylic alcohol unit of 2 can be selectively protected with modest chemoselectivity as TBS ethers . We have examined this reaction in greater depth and report herein that optimal selectivity (≥95:5) is achieved by treating sterically unbiased diols 2 and 4 with triethylsilyl chloride (TES-Cl), imidazole, and catalytic DMAP in 1:1 CH 2 Cl 2 −DMF at −78 °C.…”
mentioning
confidence: 99%
“…For the biological properties of 1,5-diols, see: Flamme & Roush (2005); Hansen et al (2003); Huang et al (2009); Oger et al (2010). For details of the synthesis, see: Ceylan & Gezegen (2008); Gezegen et al (2010).…”
Section: Related Literaturementioning
confidence: 99%